The Effect of Marketing Communication on the Performance of Academy of Secretary and Management of Taruna Bakti (ASMTB) - Mulyaningsih (International Journal of Science and Society, 2019)
This research describes the influence of marketing communication on the promotional team's performance at the Academy of Secretary and Management of Taruna Bakti. The research aims to measure the effectiveness of marketing communication to the getting of students and to know if there is a hidden influence between marketing communication and its execution in ASMTB. The method used in this research is descriptive analysis. Further, this research is equipped with path analysis to analyze the data. The results show some staggering findings. First, there is a strong relationship between marketing communication and the business world that used ASMTB's alumnae. The relation is 0.997, and if it is interpreted, the connection is solid. Second, there is also a relationship between marketing communication and potential students that will enter ASMTB. The relation is 0.151, and if it is interpreted, the relation is very weak. The last is, there is a close relationship between marketing communication and the alumnae. The relation is 0.345, and if it is interpreted, the relation is very week.